2020
DOI: 10.3389/fmars.2020.582818
|View full text |Cite
|
Sign up to set email alerts
|

Foraminiferal Ecology and Role in Nitrogen Benthic Cycle in the Hypoxic Southeastern Bering Sea

Abstract: Southeastern Bering Sea is one of the highest surface productivity area in the open ocean due to strong upwelling along the Bering canyon. However, the benthic geochemistry and organisms living in the area have been largely overlooked. In August 2017, surface sediment was sampled from four stations along a transect at depths between 1536 and 103 meters in the Bering canyon with JAMSTEC R/V Mirai. Bottom-water hypoxia was recorded in the two deepest stations (1536 and 536 m). At these stations, the oxygen penet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 106 publications
(165 reference statements)
0
4
0
Order By: Relevance
“…In our study, benthic foraminifera improved the pore-water oxygenation, and their burrows might also affect a series of diagenetic processes. Indeed, coastal foraminifera are known to accumulate large amounts of nitrate in their cells Langlet et al, 2014;LeKieffre et al, 2022) and deep-sea foraminifera can reduce nitrate and greatly contribute to benthic denitrification (Langlet et al, 2020;Choquel et al, 2021). Our results suggest that foraminiferal bioturbation also affected the benthic nitrogen cycle since lower total nitrogen (TN) content were measured in sediments bioturbated by foraminifera in comparison with non-bioturbated sediments.…”
Section: Foraminifera Modulate Anaerobic Diagenetic Processesmentioning
confidence: 57%
“…In our study, benthic foraminifera improved the pore-water oxygenation, and their burrows might also affect a series of diagenetic processes. Indeed, coastal foraminifera are known to accumulate large amounts of nitrate in their cells Langlet et al, 2014;LeKieffre et al, 2022) and deep-sea foraminifera can reduce nitrate and greatly contribute to benthic denitrification (Langlet et al, 2020;Choquel et al, 2021). Our results suggest that foraminiferal bioturbation also affected the benthic nitrogen cycle since lower total nitrogen (TN) content were measured in sediments bioturbated by foraminifera in comparison with non-bioturbated sediments.…”
Section: Foraminifera Modulate Anaerobic Diagenetic Processesmentioning
confidence: 57%
“…In our study, benthic foraminifera improved the pore-water oxygenation, and their burrows might also affect a series of diagenetic processes. Indeed, coastal foraminifera are known to accumulate large amounts of nitrate in their cells (Geslin et al, 2014;Langlet et al, 2014;LeKieffre et al, 2022), and deep-sea foraminifera can reduce nitrate and greatly contribute to benthic denitrification (Langlet et al, 2020;Choquel et al, 2021). Our results suggest that foraminiferal bioturbation also affected the benthic nitrogen cycle via enhancing microbial OM degradation, since lower total nitrogen (TN) content was measured in sediments bioturbated by foraminifera in comparison with control sediments.…”
Section: Foraminifera Modulate Anaerobic Diagenetic Processesmentioning
confidence: 69%
“…Globobulimina pacifica is also a deep-infaunal species known to thrive in low-oxygen conditions (e.g., Corliss, 1985;Jorissen et al, 1995;Fontanier et al, 2002). This species can collect nitrate and denitrify (Table 2; Langlet et al, 2020). In previous studies, genus Globobulimina has been shown to perform complete denitrification itself (Woehle et al, 2018) and contain intracellular bacteria only in low abundance, suggesting a lack of bacterial endobionts (Risgaard-Petersen et al, 2006).…”
Section: Species-characteristic Foraminiferal Bacterial Microbiomementioning
confidence: 99%
“…During the KM19-07 cruise in 2019, onboard analyses of a core (SB19; Table 1) for both dissolved pore water oxygen and nutrients (nitrite, nitrate, and ammonium) were carried out as described in Langlet et al (2020). In brief, oxygen micro-profiling was carried out in a cold room at 4°C immediately after sediment sampling.…”
Section: Pore Water Sampling and Analysesmentioning
confidence: 99%
See 1 more Smart Citation